2020
DOI: 10.1177/0022427819897932
|View full text |Cite
|
Sign up to set email alerts
|

Education versus Punishment? Silo Effects and the School-to-prison Pipeline

Abstract: Objectives: This article examines the influence of social context on punishment decisions. To this end, we present a theoretical framework to identify outcomes that can occur when police and probation officers work in schools. Method: The proposed framework draws on organizational theory as well as scholarship on school discipline and punishment and the effects of placing officers in schools. It also draws from insights gathered from site visits, interviews, and focus groups conducted as part of a process eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The school-to-prison pipeline (STPP) is a construct used to describe policies and practices, especially with respect to school discipline, in the public schools and juvenile justice system that decrease the probability of school success for children and youth, and increase the probability of negative life outcomes, particularly through involvement in the juvenile justice system. (p. 546) An integral piece to the school-to-prison pipeline is this idea of "criminalization of school discipline" (Brent, 2016;Hirschfield 2008;Hirschfield & Celinska, 2011) which involves, as Brown et al (2020) describes, "adopted approaches, such as security measures and punitive sanctions, that reflected an emphasis on punishment rather than education" (p. 406). Research has shown that students of color are disproportionately affected by school disciplinary actions (Leiber, 2002;Annamma et al, 2014;Archer, 2009;Dutil, 2020).…”
Section: Literature Review the School-to-prison Pipeline And Criminalization Of Young Black Girlsmentioning
confidence: 99%
“…The school-to-prison pipeline (STPP) is a construct used to describe policies and practices, especially with respect to school discipline, in the public schools and juvenile justice system that decrease the probability of school success for children and youth, and increase the probability of negative life outcomes, particularly through involvement in the juvenile justice system. (p. 546) An integral piece to the school-to-prison pipeline is this idea of "criminalization of school discipline" (Brent, 2016;Hirschfield 2008;Hirschfield & Celinska, 2011) which involves, as Brown et al (2020) describes, "adopted approaches, such as security measures and punitive sanctions, that reflected an emphasis on punishment rather than education" (p. 406). Research has shown that students of color are disproportionately affected by school disciplinary actions (Leiber, 2002;Annamma et al, 2014;Archer, 2009;Dutil, 2020).…”
Section: Literature Review the School-to-prison Pipeline And Criminalization Of Young Black Girlsmentioning
confidence: 99%